Scottish Art in the Industrial Age, 1800-1914.
1 online resource (424 pages)
Keywords: This volume introduces key artists such as the Scottish Pre-Raphaelites and the Glasgow Boys and engages with the critical debates and artistic theories that were circulating in the second half of the nineteenth century. This was a period when Scotland was experiencing huge growth and economic expansion and centres such as Edinburgh and Glasgow saw the emergence of the Glasgow Institute for the Fine Arts and of smaller artists' clubs, providing new opportunities for women. Artists adopted a more international outlook, travelling to Europe for training, or to work at one of the many artists' colonies, such as Grez-sur-Loing, south of Paris. Through enrolling at studios such at the Acad?????mie Julien, they were introduced to new ways of painting, thinking about art in terms of 'tonalism' and 'impressionism'. Accompanied by extensive editorial commentary, this collection will be of great interest to students of Art History and Scottish History.